2021
DOI: 10.3390/cancers13215550
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy in Patients with Metastatic Melanoma Treated with Ipilimumab and Nivolumab Who Did or Did Not Discontinue Treatment Due to Immune-Related Adverse Events: A Real-World Data Study

Abstract: Immune-related adverse events (irAEs) are very prevalent when treating patients with ipilimumab and nivolumab in combination, and 30–40% of patients discontinue the treatment for this reason. It is of high clinical relevance to investigate the consequences of discontinuing the treatment early since combination therapy with ipilimumab and nivolumab is the first line of treatment for many patients with metastatic melanoma. In this follow-up study, with real-world data from the nationwide DAMMED database, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…These results are consistent with previous reports in patients who discontinued dual nivolumab plus ipilimumab due to TRAEs, including data from CheckMate 227 and from patients with advanced sarcomatoid renal cell carcinoma in CheckMate 214. 8 37 Similar findings have been reported recently from a real-world data analysis in melanoma 38 and NSCLC, 39 40 which showed that patients may experience a durable response even after discontinuing immunotherapy for any reason or due to adverse events.…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with previous reports in patients who discontinued dual nivolumab plus ipilimumab due to TRAEs, including data from CheckMate 227 and from patients with advanced sarcomatoid renal cell carcinoma in CheckMate 214. 8 37 Similar findings have been reported recently from a real-world data analysis in melanoma 38 and NSCLC, 39 40 which showed that patients may experience a durable response even after discontinuing immunotherapy for any reason or due to adverse events.…”
Section: Discussionsupporting
confidence: 82%
“…However, up to or over 15 patients can be expected to suffer grade 3 to 4 adverse events 31–33 . If ipilimumab is combined with PD‐1 therapy, up to 50 patients could be expected to discontinue therapy because of adverse events 34,35 . The impact of immune related adverse events associated with PD‐1 therapy has been identified, including the prolongation of these events following drug cessation 36 .…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] If ipilimumab is combined with PD-1 therapy, up to 50 patients could be expected to discontinue therapy because of adverse events. 34,35 The impact of immune related adverse events associated with PD-1 therapy has been identified, including the prolongation of these events following drug cessation. 36 Thus, the potential risk of patient harm may outweigh the benefit for these young very low-risk patients.…”
Section: -Year-old Patients Standardized Hazard Ratiosmentioning
confidence: 99%